Electrode for electrolytic capacitor, method for manufacturing the same, and electrolytic capacitor
By using a chemical conversion solution containing a nitric acid compound to perform chemical conversion treatment of the electrode, an oxidized coating is formed, and the problem of leakage current of the existing electrolytic capacitor is solved and better capacitor performance is achieved.
Patent Information
- Application Number
- CN202180016881.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2021-02-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-02-10
AI Technical Summary
The existing electrolytic capacitors using an oxidized coating formed by an aqueous phosphoric acid solution are prone to leakage current problems.
The chemical conversion liquid containing nitric acid compound is used to perform the chemical conversion treatment of the electrode to form an oxidized coating, and the concentration of the nitric acid compound and the temperature of the chemical conversion liquid are controlled to inhibit the infusion of phosphorus and improve the properties of the oxidized coating.
It effectively suppresses leakage current of the electrolytic capacitor and improves the performance of the capacitor.
Smart Images

Figure CN115176322B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode for an electrolytic capacitor, a method for producing the same, and an electrolytic capacitor. Background Art
[0002] As the anode body of the capacitor element, a metal foil or a porous sintered body containing a valve metal is used. An oxide film is formed on the surface of the metal foil or the porous sintered body by chemical conversion treatment. In the chemical conversion treatment, a phosphoric acid aqueous solution is generally used (Patent Document 1, etc.).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-77257 Summary of the invention
[0006] Problems to be solved by the invention
[0007] An electrolytic capacitor having an oxide film formed using a phosphoric acid aqueous solution may have a large leakage current.
[0008] Means for solving problems
[0009] A first aspect of the present invention relates to a method for manufacturing an electrode for an electrolytic capacitor, which comprises the following chemical conversion step: a current is passed through a metal material containing a valve-acting metal in a chemical conversion solution containing an electrolyte to form an oxide film on the surface of the metal material, the chemical conversion solution containing a nitric acid compound as the electrolyte at a concentration of 0.03 mass % or more, and the concentration of the phosphorus compound in the chemical conversion solution is less than 0.01 mass %.
[0010] A second aspect of the present invention relates to a method for manufacturing an electrode for an electrolytic capacitor, which comprises the following chemical conversion step: a current is passed through a metal material containing a valve-acting metal in a chemical conversion solution containing an electrolyte to form an oxide film on the surface of the metal material, the chemical conversion solution contains a nitric acid compound as the electrolyte, the concentration of the phosphorus compound in the chemical conversion solution is less than 0.01% by mass, and the temperature of the chemical conversion solution in the chemical conversion step is above 40°C.
[0011] A third aspect of the present invention relates to an electrode for an electrolytic capacitor, comprising a metal material including a valve-acting metal, and an oxide film formed on a surface of the metal material, wherein the phosphorus concentration of the oxide film measured by energy dispersive X-ray spectroscopy is below a detection limit.
[0012] A fourth aspect of the present invention relates to an electrode for an electrolytic capacitor, comprising a metal material including a valve-acting metal, and an oxide film formed on a surface of the metal material, wherein the fragmentation peak intensity of phosphate ions of the oxide film obtained by time-of-flight secondary ion mass spectrometry is below the detection limit.
[0013] A fifth aspect of the present invention relates to an electrode for an electrolytic capacitor, comprising a metal material including a valve action metal, and an oxide film formed on a surface of the metal material, wherein the oxide film includes a tantalum oxide, and in a spectrum of the oxide film obtained by electron energy loss spectroscopy, an average intensity I of a first peak observed between 530 eV and 550 eV is 1A The average intensity of the second peak observed between 560 eV and 570 eV is 2A The difference is 10% or less of the average intensity I1 of the first peak.
[0014] The sixth aspect of the present invention relates to an electrode for an electrolytic capacitor, comprising a metal material containing a valve-acting metal, and an oxide film formed on the surface of the above-mentioned metal material, the above-mentioned oxide film containing tantalum oxide, and in the spectrum of the above-mentioned oxide film obtained by electron energy loss spectroscopy, the intensity I1 of the first peak observed between 530eV and 550eV decreases as it approaches the surface of the above-mentioned metal material.
[0015] The seventh aspect of the present invention relates to an electrode for an electrolytic capacitor, comprising a metal material containing a valve-acting metal, and an oxide film formed on the surface of the above-mentioned metal material, wherein the above-mentioned oxide film contains tantalum oxide, and in the spectrum of the above-mentioned oxide film obtained by electron energy loss spectroscopy, a fourth peak adjacent to the high energy side of the third peak belonging to the Ta-N1 end is observed above 570 eV.
[0016] Effects of the Invention
[0017] According to the present invention, an electrolytic capacitor with suppressed leakage current can be obtained.
[0018] The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a cross-sectional view schematically showing a capacitor element according to one embodiment of the present invention.
[0020] Figure 2 It is a cross-sectional view schematically showing an electrolytic capacitor according to one embodiment of the present invention. DETAILED DESCRIPTION
[0021] When using a phosphoric acid aqueous solution, a small amount of phosphorus atoms will be mixed into the oxide film formed. The presence of phosphorus atoms forms a conductive path in the oxide film as an insulator. In addition, by generating impurity energy levels in the band gap, electrons become easily released into the oxide film. It is believed that this generates leakage current of the electrolytic capacitor.
[0022] It was found that when a nitric acid compound is used as a chemical conversion solution, the properties of the oxide film are changed by mixing nitrogen instead of phosphorus into the oxide film formed. In particular, the leakage current can be further suppressed by controlling the concentration of the nitric acid compound or the temperature of the chemical conversion solution.
[0023] That is, the manufacturing method of the electrode for electrolytic capacitor of this scheme has the following chemical conversion step: a current is passed through a metal material containing a valve metal in a chemical conversion solution containing an electrolyte to form an oxide film on the surface of the metal material, and the chemical conversion solution contains a nitric acid compound as an electrolyte. In the first scheme, the nitric acid compound is contained in the chemical conversion solution at a concentration of 0.03 mass % or more. In the second scheme, the chemical conversion step is performed in the chemical conversion solution at a temperature of 45° C. or more.
[0024] The oxide film formed using the nitric acid compound has characteristics different from those of the oxide film formed using other chemical conversion solutions. These characteristics are more prominently exhibited by controlling the concentration of the nitric acid compound or the temperature of the chemical conversion solution as described above.
[0025] That is, the electrolytic capacitor electrode of this embodiment includes a metal material including a valve-acting metal and an oxide film formed on the surface of the metal material. The oxide film is an oxide of a metal including a valve-acting metal, for example, tantalum pentoxide.
[0026] [Method for producing an electrode for an electrolytic capacitor]
[0027] A-1. Option 1
[0028] In the chemical conversion step of the present embodiment, the chemical conversion solution containing the nitric acid compound contains the nitric acid compound as an electrolyte at a concentration of 0.03 mass % or more. This can form an oxide film while suppressing the incorporation of phosphorus.
[0029] From the perspective of easily suppressing the corrosion of production equipment and easily controlling the thickness of the oxide film, the concentration of the nitric acid compound is preferably 15% by mass or less. The concentration of the nitric acid compound is preferably 0.04% by mass or more, preferably 0.08% by mass or more. The concentration of the nitric acid compound is preferably 10% by mass or less, preferably 5% by mass or less.
[0030] It is preferable that the chemical conversion liquid contains electrolytes other than nitric acid compounds. However, the concentration thereof is preferably low. In particular, the concentration of compounds containing phosphorus is preferably low. The concentration of other electrolytes is preferably 0.01 mass % or less, more preferably 0.005 mass % or less. As other electrolytes, conventionally known electrolytes used in chemical conversion treatments can be cited. Other electrolytes are, for example, inorganic acids such as phosphoric acid and their salts, organic acids such as adipic acid and their salts, alkaline substances such as ammonia.
[0031] When compared at the same concentration and temperature, the conductivity of an aqueous solution containing a nitric acid compound is greater than the conductivity of an aqueous solution containing other electrolytes. Therefore, when a nitric acid compound is used, the chemical conversion treatment is performed efficiently.
[0032] In the present embodiment, the temperature of the chemical conversion liquid during the treatment is not particularly limited. From the viewpoint of productivity, the temperature of the chemical conversion liquid is preferably 25°C or higher, preferably 40°C or higher, and preferably 45°C or higher. From the perspective of suppressing the evaporation of the liquid and easily suppressing the corrosion of the production equipment, the temperature of the chemical conversion liquid is preferably 75°C or lower. When the concentration of the nitric acid compound is sufficiently small, for example, when the concentration of the nitric acid compound is 1% by mass or lower, the temperature of the chemical conversion liquid is preferably 70°C or lower. When the concentration of the nitric acid compound exceeds 1% by mass, the temperature of the chemical conversion liquid is preferably 55°C or lower.
[0033] A-2. Option 2
[0034] In the chemical conversion process of the present embodiment, the temperature during the treatment of the chemical conversion liquid containing the nitric acid compound is 40°C or more. In this way, it is possible to suppress the mixing of phosphorus while forming an oxide film. From the perspective of suppressing the evaporation of the liquid, easily suppressing the corrosion of the production equipment, and further facilitating the control of the thickness of the oxide film, the temperature during the treatment of the chemical conversion liquid is preferably 75°C or less. When the concentration of the nitric acid compound is 1% by mass or less, the temperature of the chemical conversion liquid is preferably 60°C or more. When the concentration of the nitric acid compound exceeds 1% by mass, the temperature during the treatment of the chemical conversion liquid is preferably 43°C or more, preferably 45°C or more. The temperature during the treatment of the chemical conversion liquid is preferably 70°C or less, preferably 68°C or less.
[0035] In this embodiment, the concentration of the nitric acid compound is not particularly limited. From the viewpoint of productivity, the concentration of the nitric acid compound is preferably 0.03% by mass or more, and preferably 0.05% by mass or more. From the viewpoint of easily suppressing corrosion of production equipment, the concentration of the nitric acid compound is preferably 15% by mass or less, and preferably 10% by mass or less.
[0036] In this embodiment, the chemical conversion solution preferably also contains an electrolyte other than the nitric acid compound, but the concentration thereof is preferably 0.01% by mass or less, and more preferably 0.005% by mass or less.
[0037] (Nitric Acid Compounds)
[0038] The nitric acid compound is not particularly limited. Examples of the nitric acid compound include nitric acid, nitrous acid, nitrates, nitrites, nitrate esters, and nitrite esters. Examples of salts of nitrates and nitrites include strontium, magnesium, calcium, barium, aluminum, zirconium, sodium, and lithium. Examples of functional groups of nitrate esters and nitrite esters include methyl, ethyl, and butyl. Among these, nitric acid is preferred from the perspective of being easily available and inexpensive.
[0039] (Metal material)
[0040] The metal material includes a porous sintered body or foil (metal foil) containing a valve metal. When a metal foil is used, its main surface can also be roughened by electrolytic etching or the like. As a result, the electrostatic capacitance of the electrolytic capacitor increases. When a porous sintered body is used, an electrode wire is planted from one side of the porous sintered body. The electrode wire is used for connection with a lead terminal.
[0041] Examples of valve metals include titanium, tantalum, aluminum, and niobium. The metal material may include one or more of the above-mentioned valve metals. The metal material may include the valve metal in the form of an alloy containing the valve metal or a compound containing the valve metal. From the perspective of chemical stability, the metal material is particularly preferably a porous sintered body containing tantalum.
[0042] The thickness of the metal material as the metal foil is not particularly limited, and is, for example, 15 μm to 300 μm. The thickness of the metal material as the porous sintered body is not particularly limited, and is, for example, 15 μm to 5 mm.
[0043] (Other chemical transformation conditions)
[0044] The chemical conversion voltage is the maximum value of the voltage applied between the metal material and the counter electrode. The chemical conversion voltage affects the thickness of the oxide film and the withstand voltage of the electrolytic capacitor. Therefore, the chemical conversion voltage can be appropriately set according to the rated voltage of the electrolytic capacitor without any particular limitation. For example, the chemical conversion voltage is preferably 5V or more. For example, the chemical conversion voltage is preferably 100V or less.
[0045] The time for maintaining the chemical conversion voltage (chemical conversion time) is not particularly limited and can be appropriately set in consideration of the thickness of the oxide film, productivity, etc. The chemical conversion time is preferably, for example, 1 hour or more. The chemical conversion time is preferably, for example, 20 hours or less.
[0046] The current density flowing in the metal material is not particularly limited and can be appropriately set in consideration of the chemical conversion time, etc. The maximum current density is, for example, 0.001 mA / cm 2 The maximum current density is, for example, 100 mA / cm 2 The following is appropriate.
[0047] [Electrodes for electrolytic capacitors]
[0048] The electrode of this embodiment has an oxide film on its surface. The oxide film is formed by oxidizing the surface of a metal material. Therefore, the oxide film contains an oxide of a valve-acting metal contained in the metal material.
[0049] The thickness of the oxide film is not particularly limited, and is appropriately set in consideration of the rated voltage of the electrolytic capacitor, etc. The thickness of the oxide film is, for example, 10 nm to 300 nm.
[0050] B-1. Option 1
[0051] In the oxide film of the present embodiment, the phosphorus concentration measured by energy dispersive X-ray spectroscopy (EDX) is below the detection limit. Such an oxide film can be formed on a metal material that has been chemically converted by a chemical conversion solution containing a nitric acid compound (hereinafter referred to as nitric acid chemical conversion).
[0052] EDX can be used in combination with a scanning electron microscope (SEM), a transmission electron microscope (TEM), or a scanning transmission electron microscope (STEM).
[0053] Phosphorus was detected in an oxide film formed by a phosphoric acid aqueous solution generally used for chemical conversion treatment (hereinafter, sometimes referred to as a phosphoric acid chemical conversion film). That is, in the phosphoric acid chemical conversion film, relatively many atoms that form a conductive path are mixed. On the other hand, nitrogen atoms were basically not confirmed (below the detection limit). Phosphorus was detected more near the surface of other oxide films.
[0054] In the oxide film of this embodiment, phosphorus atoms are hardly found, and a small amount of nitrogen atoms are mixed in. Therefore, it has properties different from those of a phosphoric acid chemical conversion film, and it is easy to suppress the leakage current of the electrolytic capacitor.
[0055] B-2. Option 2
[0056] In the oxide film of this scheme, the fragment peak intensity of phosphate ions obtained by time-of-flight secondary ion mass spectrometry (TOF-SIMS) is below the detection limit. That is, it means that phosphorus is less mixed into the oxide film. On the other hand, in the oxide film of this scheme, peaks estimated to be fragments of nitrogen ions are confirmed. From this, the possibility of nitrogen mixing into the oxide film is inferred. By mixing a small amount of nitrogen instead of phosphorus, the properties of the oxide film change, and the leakage current of the electrolytic capacitor can be suppressed. Such an oxide film can be formed on a metal material chemically converted by nitric acid.
[0057] If TOF-SIMS analysis is performed on other oxide films in the same manner as the EDX analysis results, the fragment peak of phosphate ions is detected. The fragment peak of ions is obtained by evaluating the surface of the oxide film. The oxide film can also be etched and evaluated internally. The internal evaluation results also have the same tendency as the surface evaluation results.
[0058] B-3. Scheme 3
[0059] The oxide film of this embodiment includes tantalum oxide.
[0060] In the oxide film of the present embodiment, the average intensity I of the first peak observed between 530 eV and 550 eV in the spectrum obtained by electron energy loss spectroscopy (EELS) is 1A The average intensity of the second peak observed between 560 eV and 570 eV is 2A The difference (=|I 1A -I 2A |) is the average intensity of the first peak I 1A That is, it satisfies 100×|I 1A -I 2A | / I 1A ≤10(%) Such an oxide film can be formed on a metal material chemically converted by nitric acid.
[0061] The first peak is attributed to the OK end (OK side. Excitation process caused by K shell electrons of oxygen). The second peak is attributed to the Ta-N1 end (Ta-N1 side. Excitation process caused by N1 shell electrons of tantalum). The relationship between the first and second peaks indicates the oxidation state of tantalum atoms.
[0062] When a chemical conversion solution containing an electrolyte other than the conventionally used nitric acid compound, for example, an inorganic acid such as phosphoric acid and its salt, an organic acid such as adipic acid and its salt, or an alkaline substance such as ammonia is used, the relationship between the first peak and the second peak in the formed oxide film (hereinafter referred to as other oxide film) does not satisfy 100×|I 1A -I 2A | / I 1A≤10(%). That is, it can be said that the oxidation state of tantalum atoms is different in the oxide film formed by chemical conversion with nitric acid and other oxide films. Although the reason is not clear at present, it is believed that this difference affects the electronic structure of the oxide film and is effective in suppressing the leakage current of the capacitor.
[0063] It can also be I 1A >I 2A , or I 1A 2A , or I 1A =I 2A .
[0064] The average intensity of the first peak I 1A The calculation is performed as follows. The intensity of the peak observed between 530 eV and 550 eV is measured at a total of 6 points, including an arbitrary point on the surface of the oxide film, 4 points that divide the thickness of the oxide film into 5 equal parts on a straight line drawn from the point toward the metal material, and the intersection of the straight line and the surface of the metal material. Furthermore, for the other 4 arbitrary points, the intensity of the peak observed between 530 eV and 550 eV at a total of 6 points with different depths is similarly measured. The average intensity I of the first peak is 1A is the average of these 30 points.
[0065] The average intensity of the second peak I 2A It is the average value of the intensity of the peak observed between 560eV and 570eV at the same 30 points as the intensity of the first peak. If there are multiple peaks observed between 530eV and 550eV, the peak on the lowest energy side can be used. If there are multiple peaks observed between 560eV and 570eV, the peak on the lowest energy side can be used.
[0066] EELS is used in combination with a scanning electron microscope (SEM), a transmission electron microscope (TEM), or a scanning transmission electron microscope (STEM).
[0067] B-4. Scheme 4
[0068] The oxide film of this embodiment includes tantalum oxide.
[0069] In the oxide film of this embodiment, the intensity I1 of the first peak observed between 530 eV and 550 eV in the spectrum obtained by EELS decreases as it approaches the surface of the metal material. In other words, it can be said that the electronic structure in the oxide film changes in the same tendency in the thickness direction. Such an oxide film can be formed on a metal material chemically converted by nitric acid.
[0070] In other oxide films, it cannot be said that the intensity I1 of the first peak is smaller the closer it is to the surface of the metal material. For example, in other oxide films, the intensity of the first peak on the surface of the metal material is sometimes greater than the intensity of the first peak inside. That is, in other oxide films, it can be said that the bonding state of oxygen changes randomly in the thickness direction. Although the reason is not clear at present, it is believed that this difference affects the electronic structure of the oxide film and is effective in suppressing the leakage current of the capacitor.
[0071] The intensity I1 of the first peak is measured at a total of 6 points, for example, including an arbitrary point on the surface of the oxide film (depth zero), 4 points (depths 1 to 4) that divide the thickness of the oxide film into 5 equal parts on a straight line drawn from the point toward the metal material, and the intersection of the straight line and the surface of the metal material (depth 5). Furthermore, for the other arbitrary 4 points, the intensity of the first peak at a total of 6 points with different depths is similarly measured. The intensities of the 5 points measured at the same depth at different locations are averaged and set as the intensity of the first peak at the depth. When there are multiple peaks observed between 530eV and 550eV, the peak on the lowest energy side can be used.
[0072] The intensity I1 of the first peak may be such that it tends to decrease as it approaches the surface of the metal material. For example, at two adjacent points of the six points from depth zero to depth 5, the intensity of the shallower point is preferably greater than or equal to the intensity of the deeper point. However, the intensity I1 at depth zero is preferably 10 Greater than the intensity I at depth 5 15 .
[0073] From the perspective of the uniformity of the oxide film quality, the intensity I at depth zero is 10 and the intensity I at depth 5 15 The difference is preferably not too large. Strength I 10 With intensity I 15 The difference (=(I 10 -I 15 )) is preferably strength I 10 That is, it is preferred to satisfy 100×(I 10 -I 15 ) / I 10 ≤30(%). More preferably, 100×(I 10 -I 15 ) / I 10 ≤20(%).
[0074] From the same point of view, the intensity I at depth 1 11 Preferably less than the intensity I at depth zero 10 , intensity I 10 With intensity I 11The difference between the strength I and the 10 With intensity I 11 The difference (=I 10 -I 11 ) is preferably of strength I 10 That is, it is preferred to satisfy 3(%)≤100×(I 10 -I 11 ) / I 10 ≤20(%). More preferably, 5(%)≤100×(I 10 -I 11 ) / I 10 ≤20(%).
[0075] B-5. Plan 5
[0076] The oxide film of this embodiment includes tantalum oxide.
[0077] In the oxide film of this embodiment, in the spectrum obtained by EELS, a fourth peak adjacent to the high energy side of the third peak attributed to the Ta-N1 end is observed at 570 eV or more. Such an oxide film can be formed on a metal material chemically converted by nitric acid.
[0078] The third peak is attributed to the Ta-N1 end (excitation process caused by the N1 shell electrons of tantalum). The position of the fourth peak indicates the state of the distance between oxygen atoms. The displacement of the fourth peak to the high energy side means that the distance between oxygen atoms is reduced. That is, it is speculated that the density of the oxide film is improved. The third peak is consistent with the second peak in the third scheme.
[0079] The fourth peak in other oxide films is observed at an energy side lower than 570 eV. That is, it can be said that the oxidation state of tantalum atoms is different in the oxide film formed by nitric acid chemical conversion and other oxide films. Although the reason is not clear at present, it is believed that this difference affects the electronic structure of the oxide film and is effective in suppressing the leakage current of the capacitor.
[0080] The 3rd peak and the 4th peak are identified as follows. A spectrum is obtained by EELS at a point within 10 nm from the surface of the oxide film toward the metal material (for example, a depth of 5 nm). Next, the 3rd peak belonging to the Ta-N1 end is identified. The 3rd peak usually appears at 563eV to 567eV. In addition, the 4th peak adjacent to the 3rd peak is identified. The position of the 4th peak is preferably confirmed by further evaluating the other 9 arbitrary points within a depth of 10nm of the oxide film by EELS. When the 4th peak at 8 of the arbitrary 10 points is observed to be above 570eV, it is appropriate to regard the oxide film as satisfying the 5th scheme.
[0081] (other)
[0082] In the third to fifth aspects, it is preferable that the following conditions are satisfied.
[0083] a) In the spectrum of the oxide film of the present embodiment obtained by EELS, the average intensity I of the fifth peak observed between 1770 eV and 1790 eV is 5A Lower than the average intensity of the fifth peak in other oxide films. 5R .
[0084] In particular, the average intensity I 5A With the average intensity I 5R The difference (=I 5R -I 5A ) is preferably an average intensity I 5R That is, it is preferred to satisfy (I 5R -I 5A ) / I 5R ≥0.1.
[0085] The fifth peak is attributed to the Ta-M5 end (the excitation process caused by the M5 shell electrons of tantalum).
[0086] b) In the spectrum of the oxide film of the present embodiment obtained by EELS, the average intensity I of the sixth peak observed between 1830 eV and 1850 eV is 6A Lower than the average intensity of the sixth peak in other oxide films. 6R .
[0087] In particular, the average intensity I 6A With the average intensity I 6R The difference (=I 6R -I 6A ) is preferably an average intensity I 6R That is, it is preferred to satisfy (I 6R -I 6A ) / I 6R ≥0.05.
[0088] The sixth peak is attributed to the Ta-M4 end (the excitation process caused by the M4 shell electrons of tantalum).
[0089] Average intensity I 5A and average intensity I 6A Can be compared with the average intensity I 1A The average strength I of the oxide film of the comparison object is calculated in the same way. 5R and average intensity I 6R Can be compared with the average intensity I 1A Calculate similarly.
[0090] In the first to fourth aspects, it is preferable that the following conditions are satisfied.
[0091] c) The value of the current (leakage current) flowing through the electrode having the oxide film of this embodiment is 10% or more less than the leakage current value of the electrode having other oxide films. This can further suppress the leakage current of the electrolytic capacitor.
[0092] The leakage current value of the electrode of this embodiment is preferably 15% or more smaller than the leakage current value of an electrode having other oxide films, and is preferably 30% or more smaller.
[0093] The leakage current of the electrode is a current value when the electrode and the counter electrode are immersed in an aqueous electrolyte solution and a voltage of 70% of the chemical conversion voltage is applied.
[0094] The oxide film of the comparative object is formed using, for example, a chemical conversion solution containing phosphoric acid at a concentration of 0.1 mass %. The chemical conversion conditions other than the composition of the chemical conversion solution are the same as those of the oxide film of this embodiment. The chemical conversion conditions are, for example, a chemical conversion voltage of 15 V, a temperature of 60° C., and a treatment time of 10 hours.
[0095] [Electrolytic capacitors]
[0096] The electrode obtained by chemically converting the metal foil as described above is used for a capacitor element. The capacitor element comprises the above-mentioned electrodes, i.e., a first electrode and a second electrode. The second electrode comprises, for example, a solid electrolyte layer and a cathode lead layer. The leakage current of the electrolytic capacitor of this embodiment is less than 30% or more than the leakage current of the electrolytic capacitor having an electrode having other oxide films.
[0097] The electrolytic capacitor comprises, for example, one or more capacitor elements, an outer package that seals the capacitor element, and a first lead terminal and a second lead terminal. At least a portion of each lead terminal is exposed from the outer package. Such a capacitor element is, for example, in the form of a sheet or a plate.
[0098] (1st electrode)
[0099] The first electrode is a metal material having an oxide film formed as described above. The first electrode is, for example, an anode.
[0100] (Second electrode)
[0101] The second electrode includes a solid electrolyte layer and an electrode extraction layer. The second electrode is, for example, a cathode.
[0102] (Solid electrolyte layer)
[0103] The solid electrolyte layer is formed so as to cover at least a portion of the oxide film. The solid electrolyte layer may also be formed so as to cover the entire surface of the oxide film. The thickness of the solid electrolyte layer is not particularly limited.
[0104] The solid electrolyte layer includes one or more solid electrolyte layers. The solid electrolyte layer is formed, for example, of a manganese compound or a conductive polymer. As the conductive polymer, polypyrrole, polyaniline, polythiophene, polyacetylene, derivatives thereof, etc. can be used. The solid electrolyte layer containing the conductive polymer can be formed, for example, by chemically polymerizing and / or electrolytically polymerizing the raw material monomer on the oxide film. Alternatively, it can be formed by applying a solution in which the conductive polymer is dissolved or a dispersion in which the conductive polymer is dispersed on the oxide film.
[0105] (Cathode extraction layer)
[0106] The cathode lead layer may be formed so as to cover at least a portion of the solid electrolyte layer, and may be formed so as to cover the entire surface of the solid electrolyte layer.
[0107] The cathode lead layer includes, for example, a carbon layer and a metal paste layer formed on the surface of the carbon layer. The carbon layer is composed of a composition containing a conductive carbon material such as graphite. The metal paste layer is composed of a composition containing silver particles and a resin. It should be noted that the composition of the cathode lead layer is not limited to this, as long as it has a current collection function.
[0108] (Lead terminal)
[0109] The materials of the first lead terminal and the second lead terminal are not particularly limited as long as they are electrochemically and chemically stable and have conductivity, and may be metal or non-metal. Their shapes are also not particularly limited.
[0110] The first lead terminal is connected to the first electrode, and the second lead terminal is connected to the second electrode. The electrical connection between the first electrode and the first lead terminal is performed, for example, by welding them. The electrical connection between the second electrode and the second lead terminal is performed, for example, by bonding the second electrode and the second lead terminal via a conductive adhesive layer.
[0111] (Outer packaging)
[0112] The outer package covers a portion of the capacitor element and the lead terminal. Thus, the first lead terminal and the second lead terminal are electrically insulated, and the capacitor element is protected. The outer package is made of an insulating material (outer package material). The outer package material includes, for example, a cured product of a thermosetting resin or an engineering plastic.
[0113] Figure 1 1 is a cross-sectional view schematically showing a capacitor element according to the present embodiment.
[0114] The capacitor element 10 includes a first electrode 11 and a second electrode 13. The first electrode 11 includes a porous sintered body 111, an electrode wire 112 planted from the porous sintered body 111, and an oxide film 113 covering at least a portion of the porous sintered body 111. The second electrode 13 includes a solid electrolyte layer 131, a carbon layer 132, and a metal paste layer 133. The carbon layer 132 and the metal paste layer 133 function as a cathode extraction layer. Such a capacitor element 10 is roughly in the shape of a cube.
[0115] Figure 2 It is a cross-sectional view schematically showing the structure of the electrolytic capacitor of this embodiment.
[0116] The electrolytic capacitor 100 includes a capacitor element, an outer package 20 that seals the capacitor element, and a first lead terminal 30 and a second lead terminal 40 , at least a portion of which is exposed to the outside of the outer package 20 .
[0117] The wire electrode 112 and the first lead terminal 30 are electrically connected by welding, for example. The metal paste layer 133 and the second lead terminal 40 are electrically connected via an adhesive layer 50 formed of, for example, a conductive adhesive (a mixture of a thermosetting resin and carbon particles or metal particles).
[0118] In this embodiment, an electrolytic capacitor using a solid electrolyte as an electrolyte and a capacitor element sealed by an outer packaging body is listed, but it is not limited to this. The electrode of this embodiment can be applied to an electrolytic capacitor having a capacitor element and an electrolyte solution in which a first electrode and a second electrode are wound through a diaphragm. In this case, the electrode of this embodiment is used for at least one of the first electrode and the second electrode.
[0119] [Example]
[0120] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0121] 《Example 1》
[0122] Follow the instructions below to make 20 Figure 2 The electrolytic capacitor shown in Figure 1 was used to evaluate its characteristics.
[0123] (i) Fabrication of capacitor elements
[0124] (ii) Preparation of the first electrode
[0125] Tantalum metal particles are used as valve-acting metal. The tantalum metal particles are formed into a rectangular parallelepiped in such a way that one end of an electrode wire formed of tantalum is buried in the tantalum metal particles, and then the formed body is sintered in a vacuum. Thus, a precursor of a first electrode including a porous sintered body containing tantalum and an electrode wire having one end buried in the porous sintered body and the other end planted from one side of the porous sintered body is obtained.
[0126] (i-ii) Formation of oxide film
[0127] As a chemical conversion solution, a 0.06 mass % aqueous solution of nitric acid was prepared. The chemical conversion tank was filled with the chemical conversion solution, and the porous sintered body and a portion of the electrode wire were immersed. The temperature of the chemical conversion solution was 60°C. The other end of the electrode wire was connected to the counter electrode, and anodization was performed for 10 hours at a chemical conversion voltage of 15V. In this way, a uniform oxide film (thickness of about 30nm) of tantalum oxide (Ta2O5) was formed on the surface of the porous sintered body and the surface of a portion of the electrode wire, and 20 first electrodes X1 were obtained.
[0128] (i-iii) Formation of solid electrolyte layer
[0129] The porous sintered body having the oxide film formed thereon was impregnated with a dispersion containing polypyrrole for 5 minutes and then dried at 150° C. for 30 minutes to form a solid electrolyte layer on the oxide film.
[0130] (i-iv) Formation of carbon layer
[0131] A dispersion (carbon paste) in which carbon particles were dispersed in water was applied onto the solid electrolyte layer and then heated at 200° C. to form a carbon layer on the surface of the solid electrolyte layer.
[0132] (iv) Formation of Metal Paste Layer
[0133] A metal paste containing silver particles, a binder resin, and a solvent was applied to the surface of the carbon layer, and then heated at 200° C. to form a metal paste layer, thereby obtaining a capacitor element.
[0134] (ii) Fabrication of electrolytic capacitors
[0135] A conductive adhesive is applied to the metal paste layer, and the second lead terminal is joined to the metal paste layer. The electrode wire is joined to the first lead terminal by resistance welding. Next, the capacitor element joined to each lead terminal and the material of the outer package (uncured thermosetting resin and filler) are placed in a mold, and the capacitor element is sealed by transfer molding to produce an electrolytic capacitor.
[0136] 《Example 2》
[0137] Twenty first electrodes X2 were produced in the same manner as in Example 1, except that the concentration of nitric acid in the chemical conversion solution was set to 10 mass % and the temperature of the chemical conversion solution was set to 45° C., thereby producing an electrolytic capacitor.
[0138] Comparative Example 1
[0139] Twenty first electrodes Y1 were produced in the same manner as in Example 1, except that a chemical conversion solution containing phosphoric acid (concentration: 0.1 mass %) was used instead of nitric acid, thereby producing an electrolytic capacitor.
[0140] 《Comparative Example 2》
[0141] Twenty first electrodes Y2 were produced in the same manner as in Example 1, except that a chemical conversion solution containing diammonium adipate (concentration: 0.2 mass %) was used instead of nitric acid, thereby producing an electrolytic capacitor.
[0142] 《Comparative Example 3》
[0143] Twenty first electrodes Y3 were produced in the same manner as in Example 1, except that a chemical conversion solution containing ammonia (concentration: 2.5 mass %) was used instead of nitric acid, thereby producing an electrolytic capacitor.
[0144] [evaluate]
[0145] (1) Analysis of oxide film
[0146] After the oxide film is formed (i-ii), the first electrodes X1 and Y1 to Y3 are analyzed.
[0147] (1-1) EELS analysis
[0148] Spectral analysis was performed using a TEM-EELS device. The results are shown in Table 1.
[0149] Table 1
[0150] 1st electrode X1 Y1 Y2 Y3 <![CDATA[Average intensity I 1A > 6.4E+06 6.7E+06 6.3E+06 5.3E+06 <![CDATA[Average intensity I 2A > 6.3E+06 5.5E+06 5.4E+06 5.4E+06 <![CDATA[Average intensity I 3A > 6.4E+06 5.6E+06 5.5E+06 5.5E+06 <![CDATA[Average intensity I 4A > 6.5E+06 5.6E+06 5.6E+06 5.5E+06 <![CDATA[Intensity I 10 > 7.2E+06 7.1E+06 6.5E+06 4.6E+06 <![CDATA[Intensity I 11 > 6.4E+06 6.4E+06 6.1E+06 5.9E+06 <![CDATA[Intensity I 12 > 6.2E+06 6.7E+06 6.1E+06 6.1E+06 <![CDATA[Intensity I 13 > 6.2E+06 7.0E+06 6.6E+06 6.1E+06 <![CDATA[Intensity I 14 > 6.1E+06 6.5E+06 6.1E+06 3.6E+06 <![CDATA[Intensity I 15 > 6.1E+06 6.5E+06 6.4E+06 - <![CDATA[(I 1A -I 2A ) / I 1A ]]> 0.010 0.179 0.143 -0.027 <![CDATA[(I 10 -I 15 ) / I 10 ]]> 0.153 0.085 0.015 1.000 <![CDATA[(I 10 -I 11 ) / I 10 ]]> 0.111 0.099 0.062 -0.283 Location of Peak 3 566eV 564eV 566eV 566eV Location of Peak 4 572eV 569eV 571eV 572eV <![CDATA[(I 5R -I 5A ) / I 5R ]]> 0.174 - 0.022 0.065 <![CDATA[(I 6R -I 6A ) / I 6R ]]> 0.059 - -0.059 0.000
[0151] (1-2) EDX analysis
[0152] The element analysis of the surface of the oxide film in the first electrodes X1 and Y1 was performed using a TEM-EDX apparatus.
[0153] Table 2
[0154] 1st electrode X1 Y1 P concentration (atomic %) (Below detection limit) 0.9-1.1 N concentration (atomic %) 1.5 (Below detection limit)
[0155] (1-3)TOF-SIMS analysis
[0156] The surface and the inside (depth 1 nm to 10 nm) of the oxide film were analyzed using a TOF-SIMS apparatus. The oxide film was etched using an Ar gas cluster ion beam.
[0157] In the first electrodes X1 and X2, phosphate ions were not detected on the surface or inside of the oxide film (below the detection limit). In the first electrodes Y1 to Y3, phosphate ions were detected on the surface or inside of the oxide film.
[0158] (2) Leakage current
[0159] After the film formation (i-ii), the leakage current values of the first electrodes X1, Y2, and Y3 were measured.
[0160] The first electrode and the counter electrode (SUS316L) thus prepared were immersed in 0.1 wt% phosphoric acid. A voltage of 70% of the chemical conversion voltage was applied between the electrodes, and the current value flowing in the first electrode was measured to obtain its average value. The average current value of the first electrode Y1 was set to 100%, and the average current value (leakage current value) of each first electrode was obtained. The results are shown in Table 3. In Table 3, the average current value of the first electrode X2 is also shown for reference.
[0161] Table 3
[0162] 1st electrode X1 X2 Y1 Y2 Y3 Leakage current (%) 64 85 100 75 71
[0163] Industrial Applicability
[0164] The electrode produced by the method of the present invention can be used in electrolytic capacitors for various purposes because leakage current is suppressed.
[0165] The present invention has been described with respect to the presently preferred embodiments, but such disclosure is not to be construed as limiting. It is obvious to a person skilled in the art that various modifications and variations can be understood by reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and variations without departing from the true spirit and scope of the present invention.
[0166] Explanation of symbols
[0167] 100: Electrolytic capacitor
[0168] 10: Capacitor components
[0169] 11: 1st electrode
[0170] 111: Metal material (porous sintered body)
[0171] 112: Electrode wire
[0172] 113: Oxide film
[0173] 13: Second electrode
[0174] 131: Solid electrolyte layer
[0175] 132: Carbon layer
[0176] 133: Metal paste layer
[0177] 20: Outer packaging
[0178] 30: 1st lead terminal
[0179] 40: Second lead terminal
[0180] 50: Adhesive layer
Claims
1. A method for producing an electrode for an electrolytic capacitor, comprising the following chemical conversion step: passing a current through a metal material containing a valve-acting metal in a chemical conversion solution containing an electrolyte to form an oxide film on a surface of the metal material; The chemical conversion solution contains a nitric acid compound as the electrolyte at a concentration of 0.03 mass % or more, The concentration of the phosphorus compound in the chemical conversion solution is less than 0.01% by mass. The temperature of the chemical conversion liquid in the chemical conversion step is 60° C. or higher and 68° C. or lower.
2. The method for producing an electrolytic capacitor electrode according to claim 1, wherein: The concentration of the nitric acid compound is 15% by mass or less.
3. The method for producing an electrolytic capacitor electrode according to claim 1 or 2, wherein: The metal material is a porous sintered body containing tantalum.
Citation Information
Patent Citations
Method of manufacturing solid electrolytic capacitor
JP2011077257A
Producing method for solid-state electrolytic capacitor
JP2002033244A
Process of forming a solid tantalum capacitor
US4164455A